Peningkatan Pemahaman Pada Mahasiswa Mengenai Konsep Rezeki Melalui Bimbingan dan Konseling Layanan Informasi Berbasis Al-Qur’an - Zhila Jannati; Muhammad Randicha Hamandia (Kuras Institute, 2022)
The belief that sustenance has been Allah swt. determine in every human being to be very important so that greed and covetousness will not occur. This belief can also affect a person's enthusiasm, motivation and sincerity in obtaining their respective sustenance. So, there is no surrender or envy of the sustenance that is owned by others. The purpose of this study is to find out how to increase students' understanding of the concept of sustenance through information services based on the Al-Qur'an. Descriptive research method is the method that researchers use in this study. Researchers collect data using observation and interviews. The research subjects were students of the Islamic Guidance Counseling Study Program, Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. Data were analyzed using qualitative descriptive data analysis. The results of this study are (a) information services are applied by researchers through steps such as planning, organizing the elements and objectives of the service, implementation, assessment, as well as follow-up and reports, and (b) understanding of the concept of sustenance in students experiencing improvement after the Qur'an-based information service was carried out where students were able to understand what sustenance is, what is the virtue of seeking sustenance, what are the characteristics of sustenance in the Al-Qur'an, how Allah swt decrees. about sustenance, and how to open the doors of sustenance